Elastic High-Performance Covered Yarn: Fabrication, Characterization and Application (Journal of Fiber Bioengineering and Informatics, 2025)
To increase the protective capacity of yarns while maintaining human wearing comfort, pure UHMWPEfilament and Spandex were combined to fabricate an elastic high-performance covered yarn. The variouswrapping process parameters were adjusted to prepare this single-lay-covered yarn with a perfect wrappingstatus, which also can achieve the balance of strength and elasticity. It was discovered that thewrapping process seriously affected the covered yarn’s performance, and the new single-lay coveredyarn showed desirable high strength and super elasticity. The strength of covered yarns shows threetypes of trend with the twist added, including first steep (300 t/m∼400 t/m), then gentle (500 t/m∼600 t/m) and last drastic (700 t/m∼800 t/m). The covered yarn twisted at 700 t/m shows theoptimal coverage morphology, excellent elasticity, and high strength. Finally, an elastic cut-resistantfabric is practically knitted by this fabricated elastic cut-resistant composite yarn, and it presents goodflexibility and protection with Level 2 cut resistance under standard testing. The fabricated elastichigh-performance covered yarn is an ideal material for producing highly elastic protective textiles and isapplied to manufacture high-quality flexible protective equipment.